His Majesty King Rama IX’s Working Principles through an Expert Scholars Towards an Immunized Community Way - Setyang , Thawon; Phutthaburee ฺBunnuea (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2026)
This academic article aims to demonstrate the application of His Majesty King Bhumibol Adulyadej The Great’s (Rama IX) 27 principles of royal work. These principles provide actionable ideas and guidelines that enable adaptation and coping with various changes. Specifically, the 20th principle, "Understand, Access, Develop," is applied and summarized into a crucial guideline for the process of creating an "immunized" community. The methodology involved lectures from knowledgeable experts who served under His Majesty, interviews with followers of the royal project initiatives and the Chaipattana Foundation, as well as fieldwork and immersion within communities surrounding royal projects to obtain original socio-geographical data on these "immunized" communities. The findings indicate that building an "immunized" community must adhere to King Rama IX’s 27 principles. The process begins with gaining a deep understanding of the community and its development. This understanding is key to nurturing the "immunized community" way of life is a method of building community immunity to prepare for and cope with various impacts and changes that may arise, by considering potential future scenarios. This immunity is built upon four aspects: material immunity, social immunity, environmental immunity, and cultural immunity. The next step is the process of human-centered development, focusing on people to understand their relationship with culture, customs, traditions, and natural resources. This fosters a relationship of mutual dependence and reciprocal support. Community members must show kindness to one another, recognizing that we are all interconnected. Cultural traditions play a vital role in building morale, providing protection, and encouraging mutual aid and sharing. This human-centered approach is a crucial mechanism for successfully building a "immunized" community by creating complete immunity in all four aspects. The successful outcome is a community that can adapt to change and achieve sustainable self-reliance.